Bioconversion of Sugarcane Biomass into Ethanol: An Overview about Composition, Pretreatment Methods, Detoxification of Hydrolysates, Enzymatic Saccharification, and Ethanol Fermentation. (26th November 2012) - Canilha, Larissa; Chandel, Anuj Kumar; Suzane dos Santos Milessi, Thais; Antunes, Felipe Antônio Fernandes; Luiz da Costa Freitas, Wagner; das Graças Almeida Felipe, Maria; da Silva, Silvio Silvério
Abstract : Depleted supplies of fossil fuel, regular price hikes of gasoline, and environmental damage have necessitated the search for economic and eco-benign alternative of gasoline. Ethanol is produced from food/feed-based substrates (grains, sugars, and molasses), and its application as an energy source does not seem fit for long term due to the increasing fuel, food, feed, and other needs. These concerns have enforced to explore the alternative means of cost competitive and sustainable supply of biofuel. Sugarcane residues, sugarcane bagasse (SB), and straw (SS) could be the ideal feedstock for the second-generation (2G) ethanol production. These raw materials are rich in carbohydrates and renewable and do not compete with food/feed demands. However, the efficient bioconversion of SB/SS (efficient pretreatment technology, depolymerization of cellulose, and fermentation of released sugars) remains challenging to commercialize the cellulosic ethanol. Among the technological challenges, robust pretreatment and development of efficient bioconversion process (implicating suitable ethanol producing strains converting pentose and hexose sugars) have a key role to play. This paper aims to review the compositional profile of SB and SS, pretreatment methods of cane biomass, detoxification methods for the purification of hydrolysates, enzymatic hydrolysis, and the fermentation of released sugars for ethanol production.